TREATMENT OF ACUTE PROMYELOCYTIC LEUKEMIA WITH AIDA BASED REGIMEN - Hela Ben Abid; Zaher Belhadjali; Samia Menif; Naouel Ben Salah; Raihane Ben Lakhal; Lamia Aissaoui; Hend Ben Neji; Zarrouk Mohamed; Kacem Karima; Yosr Ben Abdennebi; Ramzi Ben Amor; Hèla Ghédira; et al. (Mediterranean Journal of Hematology and Infectious Diseases)
In Tunisia, the ATRA era began in 1998 with the use, consecutively, of two regimens combining ATRA and an anthracycline with cytarabine (APL93), and without cytarabine (LPA99). From 2004, 51 patients with confirmed APL either by t(15;17) or PML/RARA were treated according to the PETHEMA LPA 99 trial. Forty three patients achieved CR (86%). The remaining seven patients had early death (one died before treatment onset): four caused by differentiation syndrome (DS) and three died from central nervous system hemorrhage. Multivariate analysis revealed that female gender (P=0.045), baseline WBC> 10 G/L ( P=0.041) and serum creatinine > 1.4mg/dl ( P=0.021) were predictive of mortality during induction. DS was observed in 16 patients (32%) after a median onset time of 15 days from treatment onset (range, 2–29). Body mass index ≥ 30 (P=0.01) was the only independent predictor of DS. Occurrence of hypertensive peaks significantly predicted occurrence of DS (P=0.011) and was significantly associated with high BMI (p=0.003). With a median follow-up of 50 months, 5 year cumulative incidence of relapse, event free and overall survival were 4.7%, 74% and 78%, respectively.